Ecological Analysis of Stunted Toddler in Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
The results of the Indonesia Basic Health Survey (Riskesdas) in 2007, 2013 and 2018 showed the stuntedrate for toddlers was still above 30%. While proven poverty often comes with stunted on toddlers. Thestudy aimed to answer whether poverty factors and the availability of health services are related to theprevalence of stunted toddlers in provinces in Indonesia. This study was a secondary data analysis “Data andInformation: Indonesian Health Profile in 2017”. The results showed that the high percentage of the poorpopulation (>14.43%) was dominated by the high prevalence of stunted toddlers (22.51%-30.0%). In thecategory of health center ratio per 100 thousand high population (?4) seen dominated by the prevalence ofstunted toddlers in the high category (22.51%-0.0%). In the category of nutritionist ratio per 100 thousandhigh population (>12), it appears to be dominated by the prevalence of stunted toddler in the high category(22.51% -30.0%). In the category of midwife ratio per 100 thousand high population (>97) was dominatedby the prevalence of stunted toddler (22.51%-30.0%). It was concluded that the percentage of the poorpopulation was positively related to the prevalence of stunted toddler. While health service input factors(health center, nutritionists, and midwives) were not related to the prevalence of stunted toddlers.
Keywords: ecological analysis, stunted toddlers, health profile, poverty